Unprotected Consumers in the Digital Age: The Consumer-creditors of Bankrupt, Abandoned, Defunct and of Zombie Companies - Tibor Tajti(Thaythy) (Tilburg Law Review, 2019)
The aim of this article1 is to draw the attention of comparative scholars, researchers and policy-makers to the inferior position of consumer-creditors in bankruptcy proceedings, a topic that escaped attention during the development of financial protection of consumers in Europe. Consumers may become creditors if they prepay certain goods or services that remain undelivered following bankruptcy of a retailer or service-provider. The problem that results is that consumer-creditors are treated as unsecured creditors in bankruptcy law, who rank very low on the priority ladder and are doomed to recover only a small fraction of their claims, if anything at all. In order to fill the vacuum, the article attempts to map the real dimensions of the consumer-creditor problem first by outlining the spectrum of bankruptcy cases involving consumer-creditors and the threats to consumers inherent to abandoned and defunct companies that are usually left without assets creditors could collect upon. This includes case studies of major recent bankruptcies caused by appearance of new technologies (e.g., the collapse of UK Farepak due to appearance of Internet-based competitors) and linked abuses (web-fraudulent schemes). The second part of the article provides an overview of the regulatory responses, ranging from the prescriptive approach of US law implementing limited high priority to consumer-creditors in bankruptcy proceedings in the 1970s, the 2016 multi-pronged proposals of the UK Law Commission, to the specific regulatory responses of selected post-socialist systems, like the blocked accounts introduced by Croatia and Serbia, the forced deletions of Hungary and the special tax imposed in Slovakia.